Αφηγηματικές ικανότητες παιδιών με σύνδρομα - Τομάνι, Κριστίνα (Πανεπιστήμιο Πελοποννήσου, 2024)
This dissertation attempts to highlight the narrative abilities of school-aged children with rare genetic syndromes. The theoretical framework is based on the conceptualization of language, stages of narrative, analysis of narrative structure in terms of microstructure-macrostructure and syndromes. The research was carried out in Kalamata, where two school-age case studies, one child with Charge syndrome and one with Williams syndrome, were examined. The aim of the study was to investigate the children's narrative performance at the level of microstructure and macrostructure in storytelling and retelling. The results indicate that both children demonstrated higher performance in microstructure and macrostructure in the process of retelling stories.
Μ.Δ.Ε. 10
Keywords: γλώσσα, αφήγηση, επαναφήγηση, μικροδομή, μακροδομή, σύνδρομο Charge, σύνδρομο Williams.